Lanfranchi, Th. (ed.) (2018). Autour de la notion de “sacer” - Cavallero, Fabio (ARYS. Antigüedad: Religiones y Sociedades, 2020)
LANFRANCHI, THIBAUD (ed.). (2018). Autour de la notion de sacer. Rome: école française de Rome. 300 pp., 43,06€ [ISBN  978-2-7283- 1288-7] [Book review]